Roles of Chaperone/Usher Pathways of Yersinia pestis in a Murine Model of Plague and Adhesion to Host Cells - Hatkoff, Matthew (American Society for Microbiology, 2012)
Yersinia pestis and many other Gram-negative pathogenic bacteria use the chaperone/usher (CU) pathway to assemble virulence-associated surface fibers termed pili or fimbriae. Y. pestis has two well-characterized CU pathways: the caf genes coding for the F1 capsule and the psa genes coding for the pH 6 antigen. The Y. pestis genome contains additional CU pathways that are capable of assembling pilus fibers, but the roles of these pathways in the pathogenesis of plague are not understood. We constructed deletion mutations in the usher genes for six of the additional Y. pestis CU pathways. The wild-type (WT) and usher deletion strains were compared in the murine bubonic (subcutaneous) and pneumonic (intranasal) plague infection models. Y. pestis strains containing deletions in CU pathways y0348-0352, y1858-1862, and y1869-1873 were attenuated for virulence compared to the WT strain by the intranasal, but not subcutaneous, routes of infection, suggesting specific roles for these pathways during pneumonic plague. We examined binding of the Y. pestis WT and usher deletion strains to A549 human lung epithelial cells, HEp-2 human cervical epithelial cells, and primary human and murine macrophages. Y. pestis CU pathways y0348-0352 and y1858-1862 were found to contribute to adhesion to all host cells tested, whereas pathway y1869-1873 was specific for binding to macrophages. The correlation between the virulence attenuation and host cell binding phenotypes of the usher deletion mutants identifies three of the additional CU pathways of Y. pestis as mediating interactions with host cells that are important for the pathogenesis of plague.